Alterations of brain structure and functions in anorexia nervosa. (December 2019) - Scharner, Sophie; Stengel, Andreas
Summary: The eating disorder anorexia nervosa develops mostly in adolescent girls and young women and has the highest mortality rate among psychiatric diseases. Symptoms are caloric food restriction, body weight loss or maintained very low body weight, body image disturbance and hyperactivity. Clinically, the disease is well characterized, but the underlying pathophysiology still remains to be better described. Already several decades ago, physicians and researchers began to investigate potential causes of the disease in the brain with advancing neuroimaging techniques yielding important insights. The purpose of this short review is to summarize the current knowledge on brain alterations in anorexia nervosa and to stimulate future research. By using MRI and fMRI scans, structural and functional changes can be detected. In MRI scans the most common finding is gray and white matter reduction correlating with the extent of malnourishment and mostly reversible with recovery. Most fMRI studies performed in patients with anorexia nervosa focused on food, taste, physical appearance and social cognition. Although very different in terms of the study protocol, the most common findings are increased activation of the amygdala and altered activation of the cingulate cortex. Further research is required in order to connect the different findings to further investigate the neurobiological differences between the subtypes of anorexia nervosa.